2015
DOI: 10.1126/science.aaa6760
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization by particle attachment in synthetic, biogenic, and geologic environments

Abstract: Field and laboratory observations show that crystals commonly form by the addition and attachment of particles that range from multi-ion complexes to fully formed nanoparticles. The particles involved in these nonclassical pathways to crystallization are diverse, in contrast to classical models that consider only the addition of monomeric chemical species. We review progress toward understanding crystal growth by particle-attachment processes and show that multiple pathways result from the interplay of free-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
1,637
2
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 1,673 publications
(1,783 citation statements)
references
References 120 publications
52
1,637
2
9
Order By: Relevance
“…At higher supersaturation, we provide evidence for the formation of objects consistent with a dense liquid before the growth of solid mineral phases, which has recently been proposed to feature in a multistep CaCO 3 mineralization pathway (6,14). Amorphous CaCO 3 is commonly considered to have the formula CaCO 3 ·1 H 2 O, and to our knowledge the highest water content reported for ACC is ∼1.4 H 2 O/CaCO 3 (48), which is still clearly distinct from the 4-7 H 2 O/CaCO 3 we suggest for the DLP.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…At higher supersaturation, we provide evidence for the formation of objects consistent with a dense liquid before the growth of solid mineral phases, which has recently been proposed to feature in a multistep CaCO 3 mineralization pathway (6,14). Amorphous CaCO 3 is commonly considered to have the formula CaCO 3 ·1 H 2 O, and to our knowledge the highest water content reported for ACC is ∼1.4 H 2 O/CaCO 3 (48), which is still clearly distinct from the 4-7 H 2 O/CaCO 3 we suggest for the DLP.…”
Section: Discussionsupporting
confidence: 52%
“…CNT describes the formation of nuclei from the dynamic and stochastic association of monomeric units (e.g., ions, atoms, or molecules) that overcome a free-energy barrier at a critical nucleus size and grow out to a mature bulk phase. Calcium carbonate (CaCO 3 ) is a frequently used model system to study nucleation (3)(4)(5); however, despite the many years of effort, there are still phenomena associated with CaCO 3 crystal formation where the applicability of classical nucleation concepts have been questioned (6). These include certain microstructures and habits of biominerals formed by organisms (7), or geological mineral deposits with unusual mineralogical and textural patterns (8).…”
mentioning
confidence: 99%
“…C rystallization by particle attachment (CPA) is a common mechanism by which single crystals form in solutions (1). In contrast to classical growth processes of monomer-by-monomer addition and Ostwald ripening, CPA occurs through assembly of higher-order species ranging from multi-ion complexes (2) and polymeric clusters (3) to fully formed nanocrystals.…”
mentioning
confidence: 99%
“…5b). Together, these observations indicate that non-classical crystallization pathways involving particle attachment and liquid-like transient phases operate under the applied crowding conditions especially for charged additives De Yoreo et al 2015;Niederberger and Cölfen 2006). Although a confident conclusion cannot be drawn without screening several additives, we also note an interesting relationship between the formation of metastable mineral forms and the relative stability of prenucleation clusters .…”
Section: Crowded Solutions: On Crystallizationmentioning
confidence: 58%
“…According to the conventional theory, nucleation in a homogenous supersaturated solution occurs via stochastic microscopic density fluctuations and a balance between the bulk and surface energy of an emerging phase (Frenkel 1939). However, recent studies indicate that ion-associates such as pre-nucleation clusters and liquid-like phases play vital roles in determining nucleation phenomena associated with several minerals (Bewernitz et al 2012;De Yoreo et al 2015;Dey et al 2010;Gebauer and Cölfen 2011;Gebauer et al 2008Gebauer et al , 2014Jolivet et al 2006;Wallace et al 2013). Potentiometric titration-based studies on CaCO 3 nucleation have identified distinct crowding niches leading to either enhanced or suppressed ion-association .…”
Section: Crowded Solutions and Confinement: Impact On Nucleationmentioning
confidence: 99%